STUDENTS’ PERCEPTION AND MOTIVATION TOWARD E-LEARNING AS MEDIA IN THE ONLINE ENGLISH CLASS DURING THE COVID-19 - Putera, Alam Aji (English Edu: Journal of English Teaching and Learning, 2022)
The use of media in online learning plays an important role in the process of achieving learning goals, especially during the Covid-19 pandemic which requires schools in Indonesia to study by online. Then e-learning is becoming one solution that is considered to be able to maintain the learning process. The purposes of this study were to find out the students’ perceptions and motivation toward E-Learning as media in the online teaching English during the Covid-19 pandemic. The research was qualitative research. The subjects were the Eleventh Grade Students of MAN 1 Tapin in Academic year 2020/2021. Questionnaire and interview were used to collect the data. The data were analyzed and interpreted through qualitative procedure through. The findings indicate that the students have positive perception using online learning during the Covid-19 pandemic. Based on the results, it shows that the students’ perception about their ability, teacher role and also students’ activeness in online learning during the Covid-19 pandemic was efficient because it could become alternative way to conduct learning activity from home. The students also get positive perception because it is flexible and effective.